Accuracy of fibular sectioning and insertion into a rapid-prototyped bone plate, for mandibular reconstruction using CAD-CAM technology. Issue 1 (January 2015) - Ciocca, Leonardo; Marchetti, Claudio; Mazzoni, Simona; Baldissara, Paolo; Gatto, Maria Rosaria Antonella; Cipriani, Riccardo; Scotti, Roberto; Tarsitano, Achille
Abstract Modern techniques of mandibular reconstruction, such as CAD-CAM technology and rapid prototyping, offer new means by which reconstructive surgery can be planned to optimise aesthetic outcomes and prosthetic rehabilitation. The high degree of accuracy afforded by these approaches is principally attributable to high-precision fibular sectioning and insertion of the bone into a customised bone plate. CAD-CAM mandibular reconstruction procedures using vascularised bone free-flap transfers were performed on 10 patients with benign or malignant neoplasms. Five were not treated with the aid of CAD-CAM technology, and served as the control group. Five were scheduled for maxillofacial surgery using surgical cutting guides and customised bone plates. A generalised linear model for linear measures was used to compare the accuracy of reconstruction between the two groups. A difference, even though not significant, in the lateral shift of the mesial and distal positions of the fibular units was evident between groups. CAD-CAM-generated fibular surgical guides afford improved accuracy when used to restore native anatomy, especially in the context of mandibular arch restoration, and both operating room time and related costs are reduced during fibular sectioning.